Feebates as a fiscal measure for green transportation - Zachariadis, Theodoros; Clerides, Sofronis (My University, 2015)
Vehicle taxation based on CO2 emissions is increasingly being adopted worldwide to shift consumer purchases to low-carbon cars, yet evidence on its effectiveness and economic impact is limited. We focus on feebate schemes, which impose a fee on high-carbon vehicles and give a rebate to low-carbon cars. We estimate demand for passenger cars in Germany and simulate the impact of alternative feebate schemes on emissions, consumer welfare, public revenues and firm profits. In this way we quantify trade-offs between environmental effectiveness and fiscal and economic impact of a market-based decarbonization policy. We find that revenue-neutral feebate schemes are welfare decreasing; welfare can only increase with schemes that increase tax revenues at the expense of consumer and producer surplus. After presenting briefly the methodology and results of our work, this paper proceeds with policy conclusions and presents directions for future research, both for improving the scientific analysis of feebates and for linking the modeling work more closely to the needs of policymakers – e.g. by simulating the short-and long-term response of consumers to a continuously more stringent feebate scheme, assessing induced technological progress by manufacturers and distributional aspects of these policies.
Keywords: CO2 emissions; Feebate schemes